A review of metallic tanks for H2 storage with a view to application in future green shipping. (3rd February 2021) - Wang, Zhenzhou; Wang, Yikun; Afshan, Sheida; Hjalmarsson, Johanna
Abstract: Increasing environmental legislation necessitates action within the marine industry to reduce the emission of greenhouse gases, sulphur oxides and nitrogen oxides. Several short-term/intermediate solutions have been introduced. However, the ultimate goal is to achieve complete green shipping. Insights gained from academic and industrial activities demonstrate tangible opportunities for adopting alternative fuels and/or energy sources for future ships, amongst which hydrogen is a promising option. Large scale bunkering of hydrogen on-board marine platforms is inherently risky. To determine the best practice and limitations of current techniques, this review summarises the state-of-the-art in storing hydrogen (fuel) for ships. This review focuses on the mechanical testing, selection of materials and failure mechanisms for cryo-compressed and liquid hydrogen tanks and their insulations. The review also discusses the regulatory aspects with a particular focus on the routes to approval. Knowledge gaps are identified to facilitate further research and development in this field. Highlights: Review the state-of-the-art in storing hydrogen (fuel) on ships. Summarise material properties in cryo-compressed and liquid hydrogen environments. Comment on the regulatory aspects and routes to approval. Identify knowledge gaps to facilitate further research and development.